Information for All? The emergence of UNESCO's policy discourse on the information society (1990-2003) - Julia Pohle (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The dissertation analyses the emergence of UNESCO's policy discourse on the information society between 1990 and 2003. Taking into account the historical, political and institutional background of UNESCO and its history in the field of information and communication, the empirical analysis focuses on three different policy processes that contributed to this policy discourse: the INFOethics conference series; the creation of UNESCO's intergovernmental Information For All Programme (IFAP); and the preparation of the Recommendation concerning the promotion and use of multilingualism and universal access to cyberspace. The empirical research is based on an analytical framework that combines Argumentative Discourse Analysis (ADA) with selected concepts and tools from Actor-Network Theory (ANT). Building on extensive archive research and interviews, these approaches are combined in such a way as to make possible a detailed account of UNESCO's policy-making and to analyse the emergence of its policy discourse on the information society as the outcome of discursive struggles among networks of actors.
Additional information: Dissertationsschrift / PhD Thesis, Faculty for Economics and Social Sciences, Department of Communication Studies, Vrije Universiteit Brussel, 2016
Keywords: 300; UNESCO; information society; policy discourse; Internet policy; Actor-Network-Theory; Argumentative Policy Analysis